Announcing climate policy: Can a green paradox arise without scarcity? - Sjak Smulders; Yacov Tsur; Amos Zemel (Center for Economic Studies and ifo Institute (CESifo), 2010)
Unintended consequences of a pre-announced climate policy have been studied in a variety of situations. We show that early announcement of a carbon tax gives rise to a 'Green-Paradox', in that it increases polluting emissions in the interim period (between announcement and actual implementation), irrespective of the scarcity of fossil fuels. The phenomenon holds both when the announced implementation date is taken as a credible threat and when households are skeptical about the (political) will or capability of the government to implement the policy as announced. The paradoxical outcome is driven by consumption-saving tradeoffs facing households who seek to smooth consumption over time.
Keywords: Q43; 330; climate policy; carbon tax; green paradox; uncertainty; Ökosteuer; Staatliche Information; Steuerwirkung; Ökonomischer Anreiz; Luftverunreinigung; Kohlendioxid; Zeitpräferenz; Privater Haushalt; Theorie